In Silico Analysis of the NPC1L1 Inhibitor of Catechins from Green Tea - Susanti, Erna; Setyadini, Ellyvına (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The main contributor to cardiovascular disease is atherosclerosis. The Liver X Receptor is one of the unexplored signaling pathways in atherosclerosis that contributes to cholesterol efflux and inhibitory inflammation (LXR). Catechin, as an LXR agonist, influences the expression of the NPC1L1 protein transporter, which inhibits cholesterol absorption. The objective of this study is to predict the NPC1L1 inhibitor of Catechins from Green Tea. The role of NPC1L1 inhibitors is to prevent atherogenesis. Molecular docking is the research method used. Pyrx's Open Babel was used for analysis. Autodock vina in Pyrx was employed for docking, and Chimera v1.8 was administered for visualization. The result of molecular interaction was assigned. Pose view was used in this study. Catechins have the potential to be an NPC1L1 inhibitor, according to the findings. The main parameters used to predict the biological effect were energy bonds, hydrogen bonds, and hydrophobic interactions of molecules with NPC1L1. All Catechins isolates had low affinity energy and a strong affinity for NPC1L1. Epigallocatechin gallate (EGCG) is the most effective inhibitor because it has the lowest binding energy and the most active sites, including Gln 200, Tyr 192, Trp 202, Cys 189, Gly 207, Asp 217, Gly 190, Phe 205, Asp 208. There are hydrogen bonds at Thr 219, Ile 218, Asn 204, Asn 211, Arg 201, and Asn 204. The interaction energy between NPC1L1 and EGCG is -7.5 kCal/mol. Based on the results of the in-silico analysis, the researchers concluded that Catechins have the potential to be an NPC1L1 inhibitor. Further research into molecular dynamic simulation and in vivo analysis is required to demonstrate the synergistic effect of Catechins as an inhibitor of atherogenesis.